Valproic Acid and Carnitine Metabolism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
Plasma total, free, and acyl carnitine levels were determined in children treated with valproic acid at the Valley Children's Hospital and University of California, San Francisco, Fresno, CA.